Territorialidades e visibilidades expandidas : outras relações na linguagem da escultura em Angola - Soluelo, Manuel Benvindo (2017)
Based on the art of the Africans, this study proposes a reflection on traditional and contemporary sculpture based on the aesthetic developments contemplated in the works of some African contemporaries. It seeks to develop a sensitive and critical underst